The World “Vuca” in the Light of the Classification of Mental Illness - Shahverdyan, Gayane (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
Many things in various areas of modern life undermine undermines trust in the world`s order and common sense. History is a consistent alternation of this trust and mistrust, but in the last few decades mistrust has definitely prevailed. It is not accidentally that the modern world began to be called «VUCA» (Volatility, Uncertainty, Complexity, Ambiguity). The article shows how these four qualities affected the problem of classification of mental disorders, as well as how the semantic context of these classifications can change the view of the problem of mental health and illness. In a rigorous sense, the existing psychiatric classification has not been scientifically implemented, since its main condition – the principle of recognizing the etiology and phenomenology of the disease - not complied. Consequently, there is no a holistic consideration of the nature of the disease, that's why the author comes to the conclusion that should be considered threefold approach of the diagnostic problem, including somatic, psychological and spiritual aspects, despite the objective difficulties of integrating these approaches.  For this, it is necessary to fulfill at least two conditions. First of all, to make our notions, concepts and terms more certain, distinct and “strong”, and secondly, to have trust in our own thinking, despite the fact, that the world of “VUCA” forces not to believe in the world`s order and common sense.
Keywords: classification; DSM; diagnosis; syndrome; nosology; volatility; uncertainty; complexity; ambiguity; psychology; psychiatry; spirituality